The unique Chinese innovation pathways: lessons from Chinese small and medium sized manufacturing firms - Chung, Leanne; Tan, Kim Hua (Elsevier, 2017)
Many researchers equate the development of Chinese product innovation capabilities to Japanese and South Korean's development paths, that is, from imitation to innovation. Nonetheless, today many Chinese products have competed successfully in the global markets in terms of speed, cost, quality, and innovativeness. China's product innovation performance has gained the world's recognition. The performance of some industrial areas have also outperformed Japan and South Korea. This paper aims to understand and identify the unique phases of Chinese innovation. We collected empirical data from field studies and interviews with managers of ten small and medium enterprises (SMEs) in the Suzhou province of China. The research shows three unique Chinese innovation phases that are distinctive from the Japanese and South Korean. The results provided interesting insights into how Chinese SMEs in different industries cultivated their skills and knowledge under the three unique phases. We believe the findings contribute towards a better understanding of Chinese innovation in the context of China's evolving institutions and growing firm capabilities. Moreover, findings from this research help